Cabozantinib for previously treated radioiodine‐refractory differentiated thyroid cancer: Updated results from the phase 3 COSMIC‐311 trial. Issue 24 (19th October 2022) - Brose, Marcia S.; Robinson, Bruce G.; Sherman, Steven I.; Jarzab, Barbara; Lin, Chia‐Chi; Vaisman, Fernanda; Hoff, Ana O.; Hitre, Erika; Bowles, Daniel W.; Sen, Suvajit; Oliver, Jennifer W.; Banerjee, Kamalika; et al.
Abstract: Background: At an interim analysis (median follow‐up, 6.2 months; n = 187), the phase 3 COSMIC‐311 trial met the primary end point of progression‐free survival (PFS): cabozantinib improved PFS versus a placebo (median, not reached vs. 1.9 months; p < .0001) in patients with previously treated radioiodine‐refractory differentiated thyroid cancer (RAIR‐DTC). The results from an exploratory analysis using an extended datacut are presented. Methods: Patients 16 years old or older with RAIR‐DTC who progressed on prior lenvatinib and/or sorafenib were randomized 2:1 to oral cabozantinib tablets (60 mg/day) or a placebo. Placebo patients could cross over to open‐label cabozantinib upon radiographic disease progression. The objective response rate (ORR) in the first 100 randomized patients and the PFS in the intent‐to‐treat population, both according to Response Evaluation Criteria in Solid Tumors version 1.1 by blinded, independent review, were the primary end points. Results: At the data cutoff (February 8, 2021), 258 patients had been randomized (cabozantinib, n = 170; placebo, n = 88); the median follow‐up was 10.1 months. The median PFS was 11.0 months (96% confidence interval [CI], 7.4–13.8 months) for cabozantinib and 1.9 months (96% CI, 1.9–3.7 months) for the placebo (hazard ratio, 0.22; 96% CI, 0.15–0.32; p < .0001). The ORR was 11.0% (95% CI, 6.9%–16.9%) versus 0% (95% CI, 0.0%–4.1%) ( p = .0003) with one complete response with cabozantinib. Forty placebo patients crossed over to open‐label cabozantinib. Grade 3/4 treatment‐emergent adverse events occurred in 62% and 28% of the cabozantinib‐ and placebo‐treated patients, respectively; the most common were hypertension (12% vs. 2%), palmar–plantar erythrodysesthesia (10% vs. 0%), and fatigue (9% vs. 0%). There were no grade 5 treatment‐related events. Conclusions: At extended follow‐up, cabozantinib maintained superior efficacy over a placebo in patients with previously treated RAIR‐DTC with no new safety signals. Abstract : In the randomized, double‐blind, placebo‐controlled, phase 3 COSMIC‐311 study, cabozantinib significantly improved progression‐free survival versus a placebo at the initial data cutoff in patients with radioiodine‐refractory differentiated thyroid cancer who had been treated previously with a vascular endothelial growth factor receptor–targeted therapy. After extended follow‐up in a larger intent‐to‐treat population, cabozantinib maintained its superiority versus a placebo with no new safety signals.